Penggunaan Media Pembelajaran Holy Qur'an Pada Mata Pelajaran Pengembangan Kurikulum PAI dI SMP Plus Darus Sholah Jember - Zahro', Afifah; Sutomo, Moh; Sahlan, Moh (Edification Journal : Pendidikan Agama Islam, 2022)
This article describes a learning media The Holy Qur’an, it's application, and it's support factors as well as it's resistor factors application in SMP Plus Darus Sholah Jember. The research methods that have been used is qualitative with study design research case. The Holy Qur’an use in SMP Plus Darus Sholah Jember is independent by operate in computer respectively according teacher instructions using LCD. The Holy Qur’an is a program which serve audio visual with 30 juz al-Qur’an, makharijul huruf, sifatul huruf, tajwid, tafsir, hadits, etc. Students learn how to read and understand al-Qur’an from audio and visual that the Holy Qur’an media serve. The Holy Qur’an application in SMP Plus Darus Sholah Jember divided into three level. First is muqaddam (Class VII) who emphasized on makharijul huruf, sifatul huruf, harakat, and arabic keyboard mastery, both nonesoft khot and pure arabic. Second is murottal (Class VIII) who emphasized on writing ability using nonesoft khot and pure arabic. This level help students memory. Student can listen and simulate al-Qur’an verses that served. Third is development level (Class IX) who have ability to find argument about the laws in Islam that loaded in tafsir al-Qur’an verses as well as hadits that relevant.